Pengelolaan Dana Desa Terhadap Pembangunan Infrastruktur dan Peningkatan Ekonomi Masyarakat di Desa Moyoketen Kecamatan Boyolangu - Yeny Rohmatus Soimah; Bintis Ti’anatud Diniati; Alissa Fahrina; Natasya Sasi Kirana Putri; Tasyaa Asnal Muna (Ikatan Da'i Indonesia, 2025)
This study aims to determine the process of village fund management in supporting infrastructure development and improving the community's economy in Moyoketen Village, Boyolangu District, Tulungagung Regency. Village fund management has become a crucial aspect following the enactment of Law Number 6 of 2014, which requires village governments to implement the principles of transparency, accountability, efficiency, and the appropriateness of budget use to community needs. This study used qualitative methods through interviews with the Village Head and a search for related documents and literature. The results show that village fund management is carried out through the stages of planning, organizing, implementing, and monitoring. Obstacles that emerged include technical constraints on the Siskeudes application, delays in fund disbursement, differences in aspirations between neighborhood units (RTs), and weather factors. Overall, village fund management in Moyoketen Village has been running quite well, but still requires improvements in technical aspects and coordination so that village development can be implemented more effectively and sustainably.